A Performance Appraisal System for School Principals - Knoop, Robert; Common, Ronald W. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
The Performance Review, Analysis, and Improvement System for Educators (PRAISE) is a formative evaluation instrument designed to improve the performance of school principals. The system appears to be reliable and valid and is flexible enough to accommodate the needs of a variety of schools. Sample items and categories of the instrument include problem solving and decision making; curriculum and program development; relations with teachers; relations to parents and community; and professional qualities and competencies. Selected categories and items of the inventory system for principal performance indicators include setting and achieving goals and objectives; directing and leading; managing change and innovations; and delegating and inviting participation. The inventory system is computerized to facilitate data processing. System features include the identification of strengths and weaknesses; a two-dimensional leadership profile; experiential exercises designed to analyze one's own actions and behavior in an objective manner; summaries for any segment of a population of educators; and training plans that show training needs by priority listings. PRAISE is an evolving system that, when compared to similar appraisal systems, shows great promise. Ten references are cited. (GJ)
ERIC Note: Paper presented at the Annual Meeting of the Canadian Society for the Study of Education (Montreal, Quebec, Canada, May 28-31, 1985).
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Evaluation; Computer Oriented Programs; Data Interpretation; Elementary Secondary Education; Evaluation Criteria; Evaluation Methods; Evaluators; Foreign Countries; Formative Evaluation; Interrater Reliability; Leadership Styles; Measurement Techniques; Observation; Performance; Performance Factors; Principals; Tables (Data); Ontario; Reports, Research; Speeches/Meeting Papers